Fibre Morphology and Pulp Sheet Properties of Indian Bamboos - Singh, Man Mohan; Purkayastha, S. K.; Bhola, P. P.; Lal, Krishna; Singh, Swarna (Indian Forester, 1976)
Fibre morphology and pulp strength of twelve species of bamboos grown in the arboratum of the Forest Research Institute, Dehra Dun were studied in two sets of pulps. In all the species fibre dimensions and particularly lumen width were found to vary widely indicating highly heterogenous nature of the pulp. The fibre dimensions were also significantly different in the two sets. Parenchyma proportions were also found to be different in the two sets. No marked differences were found in the various species as regards chemical composition of either chips or pulps, as well as alkali consumed during pulping. But, wide differences were found in strength properties, in unbeaten and beaten pulps of the 12 species of bamboos studied. However, these differences were considerably reduced on beating. As the ranking of tbe species on the basis of strength in unbeaten and beaten conditions is different strength of beaten pulp cannot be predicted from the unbeaten one. Further, significant differences were observed between the two sets of pulps in both unbeaten and beaten hand sheets. No relationships could be found between the fibre characteristics and the pulp strength properties, It appears from this study that because of wide variations within a species, fibre characteristics cannot be used as a criterion for classifying the bamboos for paper and pulp production. On the basis of pulp yield, alka1i consumption and sheet properties of the 12 species, they have been graded and Dendrocalamus hamiltonii has been found to be the best.